Research trends and top cited articles on the frozen elephant trunk procedure - Serpil Şahin (Genel Tıp Dergisi)
ABSTRACT Background: Bibliometric studies can direct academics. There have been many specialties and subspecialties where bibliometric analyses have been published, but our literature search yielded no bibliometric analysis of the frozen elephant trunk (FET) procedure. The primary objective of this study was to identify the most frequently referenced papers on FET procedure research and investigate the research trends. Methods: A dataset of all scientific journals published in the English language was created using the Web of Science (WOS) database. This search was then cross-referenced with a comparable search phrase query of the Scopus Library database in order to locate any publications that could have been overlooked during the first search. Citation counts were used to rank the articles. Also knowledge maps were created using VOSviewer software, and articles and reviews pertaining to the FET procedure in CVDs were taken from the WOS Core Collection. Results: A total of 484 documents on Scopus and 494 documents on WOSpertaining to the FET procedure were included in this study. The leading countries that published most of the research were Germany, Japan, and Italy in both databases. The largest subset of the FET procedure articles was published since 2012. The most cited authors were Karck, Shrestha, and Uchida. The mean Hirsch index of the articles was 40 and 10.47 per article. Conclusion:This study offers information on the traits and standards of the FET procedure literature that has received the most citations, as well as a ranking of the most important sources for this procedure. This work provides as a guide to what constitutes a citeable FET procedure publication by offering the most important references and mostly publishing journals.